Impact of the COVID-19 pandemic on surgical outcomes in patients undergoing colorectal cancer surgery: A retrospective study and meta-analysis of data from 11,082 participants - Tang, Gang; Pi, Feng; Tao, Jie; Wei, Zhengqiang (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic is affecting the care of patients with colorectal cancer worldwide, resulting in the postponement of many colorectal cancer surgeries. However, the effectiveness and safety of performing colorectal cancer surgery during the COVID-19 pandemic is unknown. This study evaluated the impact of the COVID‑19 pandemic on surgical outcomes in patients undergoing colorectal cancer surgery. Methods: We retrospectively identified patients undergoing colorectal cancer surgery in January 21, 2019, to April 1, 2019, versus January 21, 2020, to April 1, 2020. Data regarding perioperative outcomes (postoperative complications, conversion rate, duration of surgery, intraoperative blood loss, transfusion, reoperation, intensive care, histological examination, morbidity, and length of hospital stay) were retrieved and compared between the two cohorts. A meta-analysis of 14 studies was also conducted to assess the impact of the COVID‑19 pandemic on surgical outcomes in patients undergoing colorectal cancer surgery. Results: The sample included 68 patients who underwent surgery in 2020 and 136 patients who underwent surgery in 2019. No patient was converted from laparoscopy to laparotomy or required reoperation. R0 resection was completed in all patients in both groups. There was no significant difference in postoperative complications (p = 0.508), duration of surgery (p = 0.519), intraoperative blood loss (p = 0.148), transfusion (0.217), intensive care (p = 0.379), mean lymph node yield (p = 0.205), vascular positivity rate (p = 0.273), nerve invasion rate (p = 0.713), anastomosis leak rate (p = 1), morbidity (p = 0.478), and length of hospital stay (p =0.623) between the two groups. The meta-analysis also showed no significant difference in short-term outcomes between the two groups. Conclusions: Our study shows that the COVID-19 pandemic has not led to a deterioration in the surgical outcomes of colorectal cancer surgery or reduction in the quality of cancer removal. Therefore, we do not recommend postponing elective colorectal cancer surgery during the COVID-19 pandemic.